2019
DOI: 10.1029/2018ea000479
|View full text |Cite
|
Sign up to set email alerts
|

Power Law Size Distributions in Geoscience Revisited

Abstract: The size or energy of diverse structures or phenomena in geoscience appears to follow power law distributions. A rigorous statistical analysis of such observations is tricky, though. Observables can span several orders of magnitude, but the range for which the power law may be valid is typically truncated, usually because the smallest events are too tiny to be detected and the largest ones are limited by the system size. We revisit several examples of proposed power law distributions dealing with potentially d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
105
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(108 citation statements)
references
References 140 publications
(281 reference statements)
3
105
0
Order By: Relevance
“…For a lognormal model fitted to the data for a superstorm threshold of −Dst c = 283 nT, Figure 4f, the p value is 0.97 (a high probability). But this result, like those we have previously reported for similar analyses (e.g., Love et al, 2015), is based on data that were used to estimate the model parameters-it is circular logic (we now recognize) to calculate a p value using the same data used to estimate a model's parameters (e.g., Chave, 2017, Chapter 8.2.4;Clauset et al, 2009, Section 3.4;Corral & González, 2019, Section 3.2; Steinskog et al, 2007).…”
Section: Statistical Significancesupporting
confidence: 64%
See 1 more Smart Citation
“…For a lognormal model fitted to the data for a superstorm threshold of −Dst c = 283 nT, Figure 4f, the p value is 0.97 (a high probability). But this result, like those we have previously reported for similar analyses (e.g., Love et al, 2015), is based on data that were used to estimate the model parameters-it is circular logic (we now recognize) to calculate a p value using the same data used to estimate a model's parameters (e.g., Chave, 2017, Chapter 8.2.4;Clauset et al, 2009, Section 3.4;Corral & González, 2019, Section 3.2; Steinskog et al, 2007).…”
Section: Statistical Significancesupporting
confidence: 64%
“…Consider, next, a rescaling of the power law and Fréchet distributions ( > 0) by a positive factor r, This means that the power law distribution and the extreme-value end of the Fréchet distribution are "regularly varying" (e.g., Beirlant et al, 2004, Chapter 2.9.2;Bingham et al, 1987;Zwart, 2009, Chapter 2.1), "scale-invariant," or "self-similar" (e.g., Corral & González, 2019;Ghil et al, 2011;Sornette, 2006)-that is, a scaling of the independent variable x gives a corresponding power scaling of the distribution. In contrast, the lognormal distribution does not have this self-similar property,…”
Section: Asymptotic Properties Of the Modelsmentioning
confidence: 99%
“…Specifically, it is quite unclear what it really means for a degree sequence in a given real-world network to be power-law or "close" to a power law. This lack of rigor has led and still leads to confused controversy and never-ending heated debates [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. This controversy has culminated in the recent work [20] that concluded that "scale-free networks are rare."…”
Section: Introductionmentioning
confidence: 99%
“…where the distribution of the test statistic and, from it, the p−value of the fit, p f it , is calculated using 10 4 Monte Carlo simulations [61,62]. Although some fitting procedures look for the value of m min that optimizes the fit for a given data set [61][62][63], we have opted for a fixed m min in order to compare the different subsets on the same footing. So, in all cases the exponential fit for m ≥ 3 cannot be rejected (p−value of the test larger than 0.05).…”
Section: Methodsmentioning
confidence: 99%